A Miniaturized Multiband FSS Director Using Double Layer With ICPW Technique Structure for Wireless Communication Systems - P. Chomtong; N. Somjit; P. Krachodnok; C. Mahatthanajatuphat; S. Tawatchai; P. Akkaraekthalin (IEEE Access, 2023)
This paper presents a multiband director based on the frequency selective surface (FSS) unit cell structure using the double layer with interdigital CPW (ICPW) technique. The unit cell consists of the front and the back. The front part has been designed using an ICPW technique based on a coplanar waveguide structure to enhance the capacitance between the transmission line and the semi-ground. The overall structural dimension of the unit cell can be designed to be smaller than the conventional range of $λ $ /2 to $λ $ /8, due to the influence of the slow wave effect on the capacitance of the structure. The back part is the inverted layer of the front, which alternates between substrate and copper. It is composed of a square loop resonator with a double meandering line. The capacitance generated by a double meander line enhances the capacitance in the front part, which influences the control of all resonant frequencies and increases the slow wave on the double-layer unit cell structure, resulting in a significantly reduced dimension. The resonance frequencies for the designs are 1.8 GHz (LTE), 3.7 GHz (Wi-MAX) and 5.2 GHz (WLAN), respectively. According to simulation results, the FSS can transmit all resonant frequencies. It has an overall dimension of 10.93 mm $×11.48$ mm. In addition, the FSS unit cell has been arranged as a $7× 7$ array for use as a director. The dimensions are 73.48 mm $×77.38$ mm. The FSS director will be evaluated utilizing an omnidirectional dipole antenna at the same resonant frequency as the FSS unit cell. According to both the simulated and measured outcomes, the impedance matching value is below -10 dB at the three resonant frequencies. The FSS director equipped with a dipole antenna exhibits bidirectional propagation characteristics across all resonant frequencies. The antenna gains for simulation are 3.45 dBi, 3.05 dBi, and 3.72 dBi, while the antenna gains for measurement are 3.05 dBi, 2.98 dBi, and 3.12 dBi. The findings indicate a high level of concurrence.